Selling hope? A review of current youth unemployment initiatives in Cairo - Harry Pettit (Global Labor Organization (GLO), 2018)
Young university educated Egyptians continue to face difficulties in securing employment, particularly employment that matches their skill-level and provides a solid foundation for marriage. This has direct implications for the country's social stability, and for maximisation of its labour resources. Existing initiatives – including soft-skills and entrepreneurship training, as well as a promotion of call centre work – which are designed to tackle the problem are not making a positive difference. Using eleven months of grounded qualitative research, this paper argues that they rather promote a false sense of hope to youth who become stuck in cycles of precarious work, by extending the meritocratic idea that individual hard work alone leads to success. The paper finishes by suggesting that policy-makers must focus more attention on addressing shortages in secure white-collar work, as well as inequalities in access to capital, education and social connections, instead of placing blame on `lazy' youth, in order to maximize the potential of Egypt's youth and deliver inclusive economic prosperity.
Keywords: 330; youth; unemployment; training; entrepreneurship; meritocracy; hope